Cardioprotective effects of yellowstripe scad compared to salmon among healthy overweight adults in a randomized crossover trial - Chang, Wei Lin (2019)
Fish intake may be cardioprotective, with omega-3 fatty acid as the possible major contributing nutrient. However, intervention study determining the cardioprotective effects of omega-3 rich fish is scarce. It is unclear whether yellowstripe scad (YSS) as compared with salmon, both rich in omega-3 fatty acids, have effects on cardiovascular disease (CVD) risk factors. The objective of this study was to compare the effects of YSS and salmon on selected CVD risk factors among healthy overweight adults. A randomized crossover trial with two diet periods was conducted among healthy overweight (with BMI 23.0-27.4 kg/m2) Malaysian adults aged 21-55 years. Steamed whole YSS fish or salmon fillet was given for eight weeks (3 days per week), retaining approximately 1000 mg eicosapentaenoic acid and docosahexaenoic acid (EPA+DHA) per day. Diets were switched after an 8-week washout period. Fasting blood samples were collected before and after each diet period. Biochemical changes in serum and plasma were analysed. About 98 subjects were screened for eligibility and 49 subjects were participated in the intervention (35% male and 65% female; mean age 29±7 years). Results showed that P-selectin and erythrocyte sedimentation rate (ESR) were significantly reduced from baseline following the consumption of YSS (-13.024% and - 14.76% respectively, p< .05). Conversely, salmon group had significant improvement on lipid profile [triglycerides (-15.09%), HDL-cholesterol (+3.85%), and VLDLcholesterol (-14.58%)] and inflammatory cytokines [IL-6 (-5.88%) and TNF-α (-2.19%)] (p< .05). Uric acid was increased significantly by salmon diet from 0.32±0.10 mmol/L to 0.35±0.09 mmol/L (p< .05). Greater favourable effects on triglycerides (0.09 mmol/L, 95% CI=0.06-0.22, p= .01), VLDL-cholesterol (0.04 mmol/L, 95% CI=0.03- 0.11, p= .01), and IL-6 (0.01 pg/ml, 95% CI=-0.04-0.07, p= .03) were noted in salmon group as compared with YSS. These outcomes demonstrated that short-term consumption of salmon showed more pronounced effect on lipid profile and inflammatory factors as compared with YSS. Nevertheless, the favourable changes on haematological factors exerted by YSS group might deserve same attention. The beneficial effects of YSS and salmon on selected cardiovascular risk factors were unlikely to be similar despite their comparable EPA+DHA content.